Immune Modulation of Vitamin D Levels in Pediatric Celiac Disease Patients - Jomah, Ashraf Fadhil (Universitas Muhammadiyah Sidoarjo, 2025)
General Background: Celiac disease (CD) is an autoimmune disorder triggered by gluten ingestion in genetically susceptible individuals, leading to intestinal damage, nutrient malabsorption, and systemic complications. Among its nutritional consequences, vitamin D deficiency is highly prevalent and affects bone metabolism and immune regulation. Specific Background: Serological markers such as anti-tTG and anti-EMA antibodies are established diagnostic and monitoring tools for CD; however, the relationship between antibody titer strength and vitamin D status has not been fully clarified, particularly in children. Knowledge Gap: Limited studies have quantitatively explored the association between immune response intensity and serum vitamin D concentrations in pediatric CD populations. Aims: This study aimed to investigate the relationship between the magnitude of anti-tTG/anti-EMA antibody responses and serum vitamin D levels in community-based pediatric CD patients. Results: Vitamin D concentrations were significantly lower in children with strong positive antibody responses compared to those with weak positivity (p < 0.05), suggesting an inverse correlation between immune activity and vitamin D status. Novelty: This study introduces a quantitative link between antibody response strength and vitamin D deficiency severity in pediatric CD, providing an immunologic perspective for assessing nutritional risk. Implications: The findings highlight the potential for antibody titers to serve as prognostic indicators for vitamin D deficiency, guiding early nutritional interventions and individualized patient management in clinical practiceHighlight : Strong anti-tTG and anti-EMA responses are associated with lower vitamin D levels in pediatric celiac disease. The strength of immune response may indicate susceptibility to vitamin D deficiency. Findings suggest clinical importance for early monitoring and nutritional management. Keywords : Vitamin D, Celiac Disease, Pediatric, Anti-tTG, Anti-EMA